Refleksi Penguatan Profil Pelajar Pancasila melalui Strategi Menulis Jurnal Syukur - Maryam Isnaini Damayanti; Nurul Istiq'faroh; Hendratno Hendratno; Asri Susetyo Rukmi; Zaenal Abidin; Annas Solihin (Jurnal Elementaria Edukasia, 2023)
This research discusses the implementation of students' character values with a focus on the Pancasila Student Profile through the strategy of writing a Gratitude Journal. This study utilizes a mixed-method approach, combining qualitative and quantitative methods. The research subjects were undergraduate students majoring in Elementary School Education at the State University of Surabaya. The research findings indicate that the majority of students are capable of reflecting the values of the Pancasila Student Profile in their reflective writings, particularly in aspects of faith, independence, mutual cooperation, global diversity, critical thinking, and creativity. However, improvements in language and writing style are still required. These results have significant relevance to higher education in Indonesia, highlighting the importance of character development in students and serving as a foundation for curriculum and instructional enhancements. In conclusion, the activity of writing a Gratitude Journal is effective in assisting students in reflecting character values that align with the Pancasila Student Profile.